2017
DOI: 10.3233/jad-170498
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Variability Predicts Incident Alzheimer’s Disease and Mild Cognitive Impairment Comparable to a Cerebrospinal Fluid Biomarker

Abstract: These analyses provide preliminary support for IICV as a marker of incident AD and MCI. This easily-disseminated, non-invasive marker compared favorably to well-established CSF biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 35 publications
10
53
0
Order By: Relevance
“…In contrast, predicted IICV increased with age at higher literacy levels (and for both sexes), suggesting probable worsening in memory and/or executive function relative to premorbid verbal abilities. This pattern corresponds to other studies that have shown that higher IICV (calculated using variables similar to those we used) predicts MCI, AD or AD pathology ((E. D. Anderson et al, 2016; Gleason, Norton, Anderson, Wahoske, Washington, Umucu, Koscik, Dowling, Johnson, Carlsson, et al., 2017; Holtzer et al, 2008; Koscik et al, 2016)). The former pattern suggests that future studies could examine whether the risk-indicating value of IICV varies across underlying characteristics such as sex and literacy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast, predicted IICV increased with age at higher literacy levels (and for both sexes), suggesting probable worsening in memory and/or executive function relative to premorbid verbal abilities. This pattern corresponds to other studies that have shown that higher IICV (calculated using variables similar to those we used) predicts MCI, AD or AD pathology ((E. D. Anderson et al, 2016; Gleason, Norton, Anderson, Wahoske, Washington, Umucu, Koscik, Dowling, Johnson, Carlsson, et al., 2017; Holtzer et al, 2008; Koscik et al, 2016)). The former pattern suggests that future studies could examine whether the risk-indicating value of IICV varies across underlying characteristics such as sex and literacy.…”
Section: Discussionsupporting
confidence: 91%
“…Given recent results in WRAP and other studies suggesting that higher intraindividual cognitive variability (IICV) across tests at a given visit predicts increased risk of subsequent decline or AD pathology (Anderson et al, 2016; Gleason, Norton, Anderson, Wahoske, Washington, Umucu, Koscik, Dowling, Johnson, & Carlsson, 2017; Holtzer, Verghese, Wang, Hall, & Lipton, 2008; Koscik et al, 2016), we also characterized how IICV varied by sex, literacy, APOE, and age in our sample. Specifically, we calculated “4-Test IICV” as the standard deviation of z-scores of AVLT Total and Delay, Trails B, and the Wide Range Achievement Test (3 rd ed., “WRAT”) reading recognition subtest standard score (Wilkinson, 1993); AVLT Delay, Trails B, and WRAT were Box-Cox transformed prior to z-scoring (AVLT Delay had a constant of 1 added to all scores before transformation) The WRAT Reading score when used in middle-aged and older adults is accepted as a stable proxy for premorbid verbal abilities and quality of education (Ashendorf, Jefferson, Green, & Stern, 2009; Manly et al, 2003; Olsen, Fellows, Rivera-Mindt, Morgello, & Byrd, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In our data, lower literacy was associated with steady age-related decline in 4-Test IICV with higher IICV consistently observed among women; at higher literacy levels, IICV was generally higher among men and increased with age for both sexes. Our 4-Test IICV is the same as used in previous WRAP analysis and similar to what has been used in other analyses (Holtzer et al, 2008;Anderson et al, 2016, Gleason et al, 2017 which indicate higher IICV predicts MCI and AD. As IICV is developed further as a potential cognitive marker for risk of later decline in the AD continuum, future studies should examine whether riskindicating value is constant across underlying demographics such as age, sex, and literacy.…”
Section: Discussionmentioning
confidence: 82%
“…Given recent results in WRAP and other studies suggesting that higher intraindividual cognitive variability (IICV) at a given visit predicts increased risk of subsequent decline (E. D. Anderson et al, 2016;Gleason et al, 2017;Holtzer, Verghese, Wang, Hall, & Lipton, 2008;Koscik et al, 2016), we also characterized how IICV varied by sex, literacy, APOE, and age in our sample. We calculated two versions of IICV.…”
Section: Study Protocol and Outcomesmentioning
confidence: 93%
“…IIV has traditionally been conceptualized as either "inconsistency," referring to performance fluctuations on a single task across time, or as "dispersion," referring to performance fluctuations across different tasks within a single testing occasion (Hultsch et al, 2002). Both inconsistency-related IIV and dispersion-related IIV have demonstrated clinical utility across a wide range of clinical populations, but there is accumulating evidence within the neuropsychological literature to suggest that dispersion-related IIV may be especially important and may offer a more sensitive method for evaluating cognitive dysfunction relative to mean cognitive performance (Bangen et al, 2019;Gleason et al, 2018;Jones et al, 2018). Furthermore, neuropsychologists routinely administer a wide range of tests during a single evaluation and utilize this information clinically when making diagnostic recommendations; thus, cognitive dispersion scores may be easily generated from a standard battery of tests.…”
Section: Introductionmentioning
confidence: 99%